2012
DOI: 10.1111/apa.12110
|View full text |Cite
|
Sign up to set email alerts
|

Shared physical custody after family split‐up: implications for health and well‐being in Swedish schoolchildren

Abstract: Children in shared physical custody and single-parent families are more at risk of negative outcomes compared with children in two-parent families. This association was not modified by parent-child communication in children in shared custody families, indicating that the communication equals that in two-parent family children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
4
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 20 publications
(57 reference statements)
6
30
4
6
Order By: Relevance
“…Regarding the other aspect of parents’ status we investigated, research shows that children of divorced parents are affected negatively [37,41]. Our study could not show any association between having divorced parents and a risk of self-rated mental health below mean.…”
Section: Discussioncontrasting
confidence: 70%
“…Regarding the other aspect of parents’ status we investigated, research shows that children of divorced parents are affected negatively [37,41]. Our study could not show any association between having divorced parents and a risk of self-rated mental health below mean.…”
Section: Discussioncontrasting
confidence: 70%
“…However, youth in JPC displayed somewhat higher levels than those in a nuclear family, similar to findings reported in three other studies conducted in Sweden. 173,174,234 Of note, another Swedish study found no difference between children in nuclear families and in JPC. 176 To the best of my knowledge, no study has yet investigated health complaints across different family structures, while also considering the siblings present in the household.…”
Section: Health Complaints In Adolescencementioning
confidence: 91%
“…This has been shown to be particularly applicable to girls . Other potential moderators of the relationship between school experiences and mental health are migrant status , family structure and socio‐economic status . However, an extensive review that included 30 cohort studies on this topic suggested that the link between the school environment and emotional health might be rather weak among adolescents.…”
Section: Introductionmentioning
confidence: 99%